Causes of death in a cohort treated for opioid dependence between 1985 and 2005. (9th October 2013) - Degenhardt, Louisa; Larney, Sarah; Randall, Deborah; Burns, Lucy; Hall, Wayne
Abstract Aims To examine changes in causes of death in a cohort treated for opioid dependence, across time and age; quantify years of potential life lost (YPLL); and identify avoidable causes of death. Design People in New South Wales (NSW) who registered for opioid substitution therapy (OST), 1985–2005, were linked to a register of all deaths in Australia. Setting NSW, Australia. Measurements Crude mortality rates (CMRs), age–sex‐standardized mortality rates (ASSRs) and standardized mortality ratios (SMRs) across time, sex and age. Years of potential life lost (YPLL) were calculated with reference to Australian life tables and by calculating years lost before the age of 65 years. Findings There were 43 789 people in the cohort, with 412 216 person‐years of follow‐up. The proportion of the cohort aged 40+ years increased from 1% in 1985 to 39% in 2005. Accidental opioid overdoses, suicides, transport accidents and violent deaths declined with age; deaths from cardiovascular disease, liver disease and cancer increased. Among men, 89% of deaths were potentially avoidable; among women, 86% of deaths were avoidable. There were an estimated 160 555 YPLL in the cohort, an average of 44 YPLL per decedent and an average of 29 YPLL before age 65 years. Conclusions Among a cohort of opioid‐dependent people in New South Wales, 1985–2005, almost nine in 10 deaths in the cohort were avoidable. There is huge scope to improve mortality among opioid‐dependent people.